Intra‐Operative Bioprinting of Hard, Soft, and Hard/Soft Composite Tissues for Craniomaxillofacial Reconstruction. (22nd April 2021) - Moncal, Kazim K.; Gudapati, Hemanth; Godzik, Kevin P.; Heo, Dong N.; Kang, Youngnam; Rizk, Elias; Ravnic, Dino J.; Wee, Hwabok; Pepley, David F.; Ozbolat, Veli; Lewis, Gregory S.; Moore, Jason Z.; et al.
Abstract: Reconstruction of complex craniomaxillofacial (CMF) defects is challenging due to the highly organized layering of multiple tissue types. Such compartmentalization necessitates the precise and effective use of cells and other biologics to recapitulate the native tissue anatomy. In this study, intra‐operative bioprinting (IOB) of different CMF tissues, including bone, skin, and composite (hard/soft) tissues, is demonstrated directly on rats in a surgical setting. A novel extrudable osteogenic hard tissue ink is introduced, which induced substantial bone regeneration, with ≈80% bone coverage area of calvarial defects in 6 weeks. Using droplet‐based bioprinting, the soft tissue ink accelerated the reconstruction of full‐thickness skin defects and facilitated up to 60% wound closure in 6 days. Most importantly, the use of a hybrid IOB approach is unveiled to reconstitute hard/soft composite tissues in a stratified arrangement with controlled spatial bioink deposition conforming the shape of a new composite defect model, which resulted in ≈80% skin wound closure in 10 days and 50% bone coverage area at Week 6. The presented approach will be absolutely unique in the clinical realm of CMF defects and will have a significant impact on translating bioprinting technologies into the clinic in the future. Abstract : In this study, intra‐operative bioprinting of different craniomaxillofacial tissues, including skin (soft), bone (hard), and composite (hard/soft) tissues, is demonstrated on rats in a surgical setting. The newly developed extrudable bioink supports osteogenic differentiation of progenitors and induces bone tissue formation in vivo. Furthermore, with droplet‐based bioprinting, the soft‐tissue bioink facilitates faster wound healing.